The impact of Nrf2/HO-1, PD-L1/Bax/Bcl-2 and TNF-α/Il-6 signaling pathways in the ameliorative role of cordycepin against acrylamide-induced cardiac toxicity in rats - Ahmed A. Sedik; Soha A. Hassan; Mona S. O. Gouida; Eman Khalifa (Scientific Reports)
Abstract Acrylamide (ACR) is a hazardous and possibly carcinogenic chemical compound that humans are constantly exposed to in their daily life. ACR passively affect many organ systems, including the cardiovascular system. Cordycepin (Cor) is a bioactive molecule derived from various species in the fungal kingdom, especially the genera Cordyceps and Ophiocordyceps. Cordycepin is known for its large-scale pharmacological activities. This study was conducted to evaluate the potential therapeutic effect of Cor on ACR-induced cardiotoxicity. Thirty-two Sprague‒Dawley rats were randomly divided into four groups (8 rats/group). Group I represented the control group, Group II received ACR (20 mg/kg/day) orally for 27 days, and Groups III and IV represented the control group. Rats received ACR (20 mg/kg) orally concurrently with Cor (10 and 20 mg/kg, b.w.), respectively, for 27 days. Serum cardiac biomarkers, such as cardiac troponin I (cTnI), creatine kinase (CK)-MB and lactate dehydrogenase (LDH), were evaluated. In addition, the antioxidant status and inflammatory response to ACR were evaluated. Moreover, detailed histopathological and ultrastructural observations were conducted. Our findings revealed that rats subjected to ACR presented increased levels of serum cardiac biomarkers, tumor necrosis factor-alpha (TNF-α), interleukin-6 (Il-6), malondialdehyde (MDA), annexin V, and Bax values, and programmed death ligand-1 (PD-L1) and decreased activities of nuclear factor erythroid 2-related factor 2 (Nrf-2) and heme oxygenase-1 (HO-1) and reduced glutathione (GSH), superoxide dismutase (SOD) and Bcl-2 expression. Conversely, the administration of Cor to rats treated with ACR in a dose-dependent manner succeeded in restoring serum cardiac biomarkers, modulated redox homeostasis and reduced inflammatory and apoptotic biomarkers. Consequently, a marked improvement was observed in the histopathological and ultrastructural images of the heart. In conclusion, Cor provides cardiac protection by inhibiting ACR-induced Nrf2/HO-1 and Bax/Bcl2 signaling failure, hence maintaining heart function. These findings suggest that Cor could be a promising treatment candidate for reducing ACR-induced cardiac damage.